Non-nutritive sucking associated with self-mutilating behavior - Silva, Renata Cristiane da; Jeremias, Fabiano [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Zuanon, Angela Cristina Cilense [UNESP] (My University, 2013)
Although sucking activity has been considered an essential behavior of early childhood to satisfy nutritive and non-nutritive needs, digit and pacifier sucking are deleterious oral habits that may interfere with child development. Furthermore, this clinical picture may be compounded by other concerning habits, such as self-mutilating behavior. This article reports 4-year follow-up of a child in whom non-nutritive sucking was associated with an unusual self-mutilating behavior; namely, the child would pull out her own hair after wrapping it around her finger every time she sucked on the pacifier. This occurred specially at bedtime, while she was watching TV, or when she was somewhat anxious, and remitted and recurred throughout the follow-up period. In an attempt to address this behavior, pacifier use was discontinued and the child’s head was shaved. Ultimately, the case was only solved through combined efforts involving the child, her family, and health professionals. Based on the parents’ reports and clinical examination and follow-up findings, we emphasize the importance of investigating the origin of the problem and considering emotional aspects and its association with other habits in such cases.

Apesar de a atividade de sucção ser considerada um comportamento essencial da primeira infância por satisfazer as necessidades nutritivas e não-nutritivas, a sucção do dedo e chupeta são hábitos deletérios ao desenvolvimento da criança. Além disso, esse quadro clínico pode ser ainda mais preocupante se houver associação com outros hábitos, como o da automutilação. Neste contexto, no presente artigo são relatados 4 anos de acompanhamento de uma criança que costumava arrancar seus cabelos depois de enrolá-los nos dedos enquanto estava com a chupeta na boca, sem demonstrar sinal algum de sintomatologia dolorosa. Tal fato ocorria especialmente próximo a períodos de sono, ansiedade ou quando assistia à televisão, havendo períodos de remissão e exacerbação. Na tentativa de solucionar o caso foi proposta, além da interrupção do uso da chupeta, a raspagem de todo o cabelo da criança. Contudo, a solução definitiva só foi possível quando houve o envolvimento coletivo, abrangendo criança, família e profissionais da saúde. Baseando-se no relato dos pais, no exame clínico e no acompanhamento do caso, enfatiza-se a importância de se investigar a origem do problema, considerando os aspectos emocionais e sua associação com outros hábitos.
Hábito de sucção não-nutritiva associada à automutilação
Keywords: Child; Pacifiers; Self mutilation; Criança; Chupetas; Automutilação